2004
DOI: 10.1089/154099904322836465
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Sectional Prevalence Study of Depression at Various Times after Delivery in Mersin Province in Turkey

Abstract: In this Turkish population, PPD prevalence was substantial at all time points. The prevalence was at its lowest level before the second postpartum month and increased with time. The decrease in the intensive social and physical support given to the mother immediately after delivery may explain this trend.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 24 publications
3
21
0
3
Order By: Relevance
“…Agoub, Moussaoui, & Battas, 2005) while a majority showed that the prevalence decreased overtime. In Turkey, Bugdayci, Sasmaz, Tezcan, Kurt, and Öner (2004) showed that prevalence rates increased with time elapsed since delivery.…”
Section: Prevalencementioning
confidence: 99%
See 1 more Smart Citation
“…Agoub, Moussaoui, & Battas, 2005) while a majority showed that the prevalence decreased overtime. In Turkey, Bugdayci, Sasmaz, Tezcan, Kurt, and Öner (2004) showed that prevalence rates increased with time elapsed since delivery.…”
Section: Prevalencementioning
confidence: 99%
“…Stressful life events (Abou-Saleh & Ghubash, 1997; Mohamed, et al, 2011;Agoub et al, 2005;Chaaya et al, 2002), marital difficulties (Abou-Saleh & Ghubash, 1997;Agoub et al, 2005), lack of social/emotional support (Abou-Saleh & Ghubash, 1997;Mohamed, et al, 2011;Alkar & Gencoz, 2005;Bugdayci et al, 2004;Bener et al, 2012;Chaaya et al, 2002;Azar et al, 2006) and conflict with family members (AlHinai, 2014) have been reported. In one study in the UAE, Green and colleagues (2006) found that body image and weight concerns also seemed to be stressful for postpartum women.…”
Section: Psychological Factorsmentioning
confidence: 99%
“…Dünyada gebelikte depresyon prevalansı %7-26 olarak bildirilirken (5-7) postpartum dönemde depresyon sıklığı, araştırmalarda kullanılan tanı yöntemine göre farklılık göstererek %3.5-40 arasında değişmektedir (5,(8)(9)(10)(11)(12). Türkiye'de bu sıklık %6.3-50.7'dir (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). Doğumun en sık görülen komplikasyonlarından biri olarak değerlendiri-len (9-16) postpartum depresyon (PPD) DSM-IV'de doğumu takip eden 4 hafta içerisinde ortaya çıkan majör depresyon atağı olarak tanımlanmaktadır (13).…”
Section: Introductionunclassified
“…Türkiye'de postpartum depresyon ve risk faktörleri ile ilgili pek çok çalışma bulunmakla (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) birlikte PPD'un yaşam kalitesi üzerine etkisi hakkında bir çalışma yoktur. Bu çalışmanın amacı PPD sıklığını, risk faktörlerini ve PPD'un annenin yaşam kalitesi üzerine etkisini belirlemektir.…”
Section: Introductionunclassified
“…As we only have the depression scores for 2 nd week and 6th month, we might have missed this increase. In a cross-sectional study in Turkey, depression prevalence increased in time, however that study group also included women in postpartum one year and more (27). This finding might be explained by the decrease of social and physical support in time which was provided to mother few weeks after delivery.…”
Section: Discussionmentioning
confidence: 95%